Beyond Words/Signs: DHH Learners' Spatial Reasoning in Mathematics as Embodied Cognition. - Thom, Jennifer S.; Hallenbeck, Taylor (American Annals of the Deaf)
Spatial reasoning is critical across the STEM disciplines. Examining deaf and hard of hearing (DHH) children's spatial reasoning in mathematics, particularly geometry, as an embodied phenomenon opens new possibilities for deaf education. The authors inquire into the embodied processes and forms of DHH learners' spatial reasoning, considering how such knowledge can expand access and conceptual opportunities for both DHH and hearing learners. The article focuses on the spatial reasoning of two grade 1 hard of hearing children as they complete a geometric task with a hearing peer in a mainstream classroom. Informed by research in cognitive science, mathematics, and the fields of deaf and general education, the authors explicate key spatial subcomponent processes of deconstructing and constructing as the children produce 2D and 3D figures. The findings of this qualitative study provide considerations for future research and pedagogy in both deaf and general education.